A monograph of the genus Westwoodia (Hymenoptera: Ichneumonidae) - Wharton, Robert A.; Roeder, Karl; Yoder, Matthew J. (Zootaxa, 2008)
Westwoodia (Ichneumonidae: Ctenopelmatinae) is an Australian endemic heretofore known from only two described species. Three additional species are described here: Westwoodia gauldi Wharton and Roeder, n. sp. and W. romani Wharton and Roeder, n. sp., both from southeastern Australia, and W. rodmani Wharton and Roeder, n. sp. from western Australia. A neotype is designated for W. ruficeps, following a detailed morphological comparison of topotypic material from Tasmania with populations from mainland Australia. New host records are provided; known hosts all belong to the Perginae (Hymenoptera: Pergidae). A phylogenetic analysis of relationships among species is presented along with a key to species. Species richness is greatest in southeastern Australia, which may simply represent a collecting bias.